Ethnopharmacology, phytochemistry, pharmacology and toxicity of the genus Gouania - Hannington Gumisiriza; Eunice Apio Olet; Lydia Mwikali; Racheal Akatuhebwa; Owen Kembabazi; Timothy Omara; Julius Bunny Lejju (Heliyon)
The genus Gouania (Rhamnaceae) comprises at least 50 recognized species distributed across tropical and subtropical regions. Gouania species have been ethnomedicinally used to treat a variety of ailments. Despite their widespread medicinal use, there is no comprehensive documentation that consolidates the ethnobotanical knowledge, phytochemicals, pharmacological properties, and toxicity of Gouania species. Herein, this review details the ethnopharmacology, phytochemical constituents, pharmacological properties and toxicity of Gouania species to provide perspectives for future research on this genus. Based on available literature, herbal preparations from Gouania species have been used to treat ailments related to the digestive, cardiovascular, respiratory, skin, musculoskeletal, reproductive, endocrine and urological systems. Extracts and isolated compounds from seven Gouania species (G. leptostachya, G. longipetala, G. lupulozdes, G. macrocarpa, G. longispicata, G. obtusifolia, and G. ulmifolia) have demonstrated promising anticancer, antimicrobial, antioxidant, and antiviral properties, supporting their ethnomedicinal uses. To date, 64 compounds (including 6 phenolic compounds, 24 flavonoids, and 34 terpenoids) have been isolated and characterized in the genus mainly as gouaniasides I-IX, gouanogenins, and gouanic acids. Most Gouania species remain unexplored for their potential bioactivities. The identification of more than 54 % as novel compounds from just seven Gouania species highlights the genus as a promising source for discovering new therapeutic agents to combat the growing challenge of multidrug-resistant pathogens. Conducting extensive phytochemical and pharmacological analyses across a broader array of Gouania species could unveil a more comprehensive profile of bioactive compounds, and pave way for innovative treatments against a diverse range of pathogens and diseases.